Nitrogen-doped interconnected carbon nanosheets from pomelo mesocarps for high performance supercapacitors. (1st February 2016) - Peng, Hui; Ma, Guofu; Sun, Kanjun; Zhang, Zhiguo; Yang, Qian; Lei, Ziqiang
Graphical abstract: Abstract: Here, we report a novel type of nitrogen-doped porous interconnected carbon nanosheets derived from an easily gained and green plant-waste (pomelo mesocarps) by simultaneous activation, carbonization and nitrogen-doped processes using CaCl2 as activating agent and urea as nitrogen source. The nitrogen-doped pomelo mesocarps-based nanosheet carbon (N-PMNC) displays an interconnected sheet-like morphology, a high specific surface area (974.6 m 2  g −1 ), a porous architecture and a high nitrogen doping content (9.12 wt%). The N-PMNC based supercapacitor exhibited superior electrochemical performance with high specific capacitance of 245 F g −1 at 0.5 A g −1 and excellent rate capability (72% capacitance retention ratio even at 20 A g −1 ) in 2 mol L −1 KOH electrolyte. Furthermore, N-PMNC based symmetric supercapacitor possesses high specific energy of 14.7 Wh kg −1 at a power density of 90 W kg −1 operated in the wide voltage range of 1.8 V in aqueous neutral Na2 SO4 electrolyte, and shows outstanding cyclic stability.